LINKING ISLAMIC COMMERCIAL AND SOCIAL FINANCE WITH SPECIAL REFERENCE TO CASH-WAQF AS NEW STRATEGY OF INTEREST-FREE MICRO-CREDIT FOR FAMILY EMPOWERMENT OF THE POOR TOWARDS ESTABLISHING WORLD SOCIAL BANK: A CASE STUDY APPROACH - Mannan, M.A. (Bank Indonesia, 2018)
The floating of Cash-waqf Certificate as a financial instrument by Social Islami Bank Ltd (SIBL) in Bangladesh in 1997 (formerly known as Social Investment Bank Ltd) is an innovation in the history of Islamic Finance. The issuance of Cash-waqf Certificate has settled the age-old controversy among scholars concerning the concept of perpetuity and inalienability associated with waqf property since its implementation during the Ottoman Empire in the early 15th century. This study has put forward three proposals to establish a World Social Bank that includes (i) Giving Institutional Leadership by Bank Indonesia (ii) Forming International Taskforce (iii) Connecting Initiatives of Muslim- Minorities in Non-Muslim Countries for initial establishment of Commonwealth of Human Communities. Since the aforementioned Cash Waqf is managed by the Bank, it has its transparency and accountability, it is a perpetual deposit and its profit can be invested in a wide spectrum of social investment. Bank shall manage Cash-Waqf on behalf of the Waqif. It can help monetizing Islamic Voluntary Sector, accumulation of Social Capital and National wealth, implementing strategic social investment program that reinforces family values, family heritage empower people at grass roots and stimulates economic, social and moral foundation of a caring society. Cash-Waqf Certificate provides new opportunities to transfer liquid asset and make connection with one another on a global scale leading to establishment of World Social Bank a new strategy of interest-free micro-credit for empowering the poor to irrespective of caste,creed and religion.